Evaluating Solutions on Congeal Oil Problem Using Analytical Hirarchy Process (AHP): Case Study of Chevron - Sapoetra, Tri Djaka; Novani, Santi (The Indonesian Journal of Business Administration, 2016)
Abstract. Steam flood serves to reduce the viscosity of which is contained in the oil, so oil has dropped its viscosity will be easily lifted to the surface using a pump. In reality, not all the oil will go down viscosity. There are some who still viscous oil where oil has a pour point that is high enough, so that the oil needs treated specifically to be lifted to the surface. This is what is referred to as congeal Oil. There are several ways to resolve this matter, i.e, Steam Injection through production line, chemical Continues injection through production line, solvent treatment through wellbore and down hole equipment installation through tubing. The decision-making process uses Analytic Hierarchy Process (AHP) and Value-Focused Thinking (VFT) to select the best solutions for Congeal Oil Problem in Heavy Oil Characteristic. Based on the AHP methods and the result interview from experts and calculations analysis, the best solution in Ã¢â‚¬Å“Decision Analysis on Congeal Oil Problem in Heavy Oil CharacteristicÃ¢â‚¬Â is Ã¢â‚¬Å“Chemical continues injection through production lineÃ¢â‚¬ÂÃ‚Â Keywords: congeal oil, decision analysis, heavy oilÃ‚Â Abstract. Steam flood serves to reduce the viscosity of which is contained in the oil, so oil has dropped its viscosity will be easily lifted to the surface using a pump. In reality, not all the oil will go down viscosity. There are some who still viscous oil where oil has a pour point that is high enough, so that the oil needs treated specifically to be lifted to the surface. This is what is referred to as congeal Oil.There are several ways to resolve this matter, i.e, Steam Injection through production line, chemical Continues injection through production line, solvent treatment through wellbore and down hole equipment installation through tubing.The decision-making process uses Analytic Hierarchy Process (AHP) and Value-Focused Thinking (VFT) to select the best solutions for Congeal Oil Problem in Heavy Oil Characteristic. Based on the AHP methods and the result interview from experts and calculations analysis, the best solution in Ã¢â‚¬Å“Decision Analysis on Congeal Oil Problem in Heavy Oil CharacteristicÃ¢â‚¬Â is Ã¢â‚¬Å“Chemical continues injection through production lineÃ¢â‚¬ÂÃ‚Â Keywords: congeal oil, decision analysis, heavy oil